Pengaruh Model Pembelajaran Quantum Teaching terhadap Minat Belajar Siswa pada Sub Tema 2 Peristiwa Kebangsaan Seputar Proklamasi Kemerdekaan Kelas V UPTD SDN 124394 Siantar Timur - Indah Purba; Nancy Angelia Purba; Minar Trisnawati Lumbantobing (Departement of Mathematics Education, 2023)
This study aims to determine the influence of the Quantum Teaching learning model on the learning interest of grade V students of UPTD SD Negeri 124394 Siantar Timur for the 2022/2023 academic year. The research hypothesis is that there is a significant influence between the Quantum Teaching learning model on the learning interest of grade V students of UPTD SD Negeri 124394 Siantar Timur for the 2022/2023 academic year. This research is a descriptive quantitative research. The population in this study was all class V students totaling 50 people using the entire population as a research sample. The data collection process uses observational instruments, questionnaires and documentation, using instrument test data analysis techniques, prerequisite tests, descriptive statistics and hypothesis tests. The results of this study showed that thevalue of t count ˃ ttable is 2.042 > 2.021 with a significance value of 0.047 < 0.05. Then it can be concluded that Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the research hypothesis: